The Anthropocene Is More Than a Time Interval - Matthew Edgeworth; Andrew M. Bauer; Erle C. Ellis; Stanley C. Finney; Jacquelyn L. Gill; Philip L. Gibbard; Mark Maslin; Dorothy J. Merritts; Michael J. C. Walker (Earth's Future)
Abstract Following the recent rejection of a formal Anthropocene series/epoch by the Subcommission on Quaternary Stratigraphy (SQS) of the International Commission on Stratigraphy (ICS), and its subsequent confirmation by the International Union of Geological Sciences (IUGS), the opportunity arises to reset the definition of the Anthropocene. The case for informally recognizing the Anthropocene to be a major planetary event of Earth system transformation offers a promising way forward, but this has been criticized by proponents of an Anthropocene series/epoch. In order to move on from the assumption that it must be a time interval, and to foster a more transdisciplinary and inclusive approach, the main points of the critique must be directly addressed.